Growth in Unemployment Raises Poverty Rates: Most Low-Wage Earnings Constitute Supplement to Primary Household Income - Jan Goebel; Peter Krause; Jürgen Schupp (Weekly Report, 2005)
Inequality with respect to personal earned income has increased in recent years. This trend has gone hand in hand with changes in both the employment constellations of households and the labor market activity of individuals (e.g. through 'minijobs'). In particular, the years since 2000 have seen a rise in the share of households with no market income because their members are either registered or hidden unemployed. These findings do not necessarily indicate an increase in relative poverty, because the latter depends on net household income and not just on individual primary incomes. While the risk of poverty also increased in recent years amongst low-wage earners, the rise only applied to those 47% of low-wage earners who live in households without another gainfully employed household member. More than half of all low-wage earners live in households that have a below-average risk of poverty. Unemployment still represents the principal risk factor for poverty. Whereas the likelihood of being poor in the event of unemployment was 29% in 1993, this risk had increased by ten percentage points by 2003. For an unemployed person living alone or whose spouse or partner was not working, the risk of poverty in 2003 was a substantial risk of 53%.
Keywords: 330